Flow analysis and shear rate comparison of counter-rotating and co-rotating intermeshing twin-screw extruders for filament extrusion of polypropylene-based biocomposites - Abdul Kudus, Syahibudil Ikhwan; Syah Lubis, Abdul Munir Hidayat; Amran, Ammar Syafi; Mustafa, Nuzaimah; Mohammad Taha, Mastura; Shaharuzaman, Mohd Adrinata (Universiti Putra Malaysia Press, 2024)
This study investigates and compares the performance of counter-rotating and co-rotating intermeshing twin-screw designs in filament extruder machines. The research sought to determine whether the counter-rotating intermeshing design with its opposite flow direction offers advantages over the co-rotating intermeshing design in terms of flow analysis and shear rates. Flow analysis was conducted to examine the velocity of the polypropylene-based biocomposite material inside the barrel. Shear rate data was obtained by evaluating the relationship between shear rate and screw speed to assess the stability and maximum shear rate of the twin-screw extruders. The results revealed that the counter-rotating intermeshing twin-screw extruders exhibited higher shear rates and more consistent pressure compared to the co-rotating intermeshing design. The superiority of the counter-rotating extruder was attributed to its opposite flow direction and distinct thread shapes, facilitating efficient material compression and improved dispersion of polymer-based biocomposite materials. The study suggested the potential for further exploration and refinement of the counter-rotating intermeshing twin-screw extruder design, particularly in producing polypropylene-based biocomposite filaments for Fused Deposition Modeling (FDM) machines